Driving change in manufacturing quality systems by selecting best-fit off-the-shelf software platform. (11th May 2006) - Yadav, Om Prakash; Bilen, Canan; Solanki, Rajesh
The traditional approach to developing a quality system has been to build it around existing software. Little consideration is given to understanding operational and business requirements of quality systems. Current customers and industry trends, however, suggest an increasing role for effective quality management systems in achieving competitive advantage. This paper presents a systematic top-down approach for the design of requirement-driven quality systems and subsequent selection of the best-fit off-the-self software. The proposed approach captures a company's operational and business goals, and develops a comprehensive list of quality system requirements. These requirements are prioritised and classified based on the Kano model. The best-in-class technical features necessary to fulfill quality system requirements are explored and identified. QFD is used to link company requirements with technical features. Finally, using the Pugh methodology, the best-fit software platform is selected. The proposed methodology has been validated and implemented at a leading global manufacturing company.